Mechanical properties and formability of EN AW-7075 in cold forming processes. Issue 1 (November 2020) - Behrens, B-A; Hübner, S; Vogt, H; Golovko, O; Behrens, S; Nürnberger, F
Abstract: Due to a low density and high tensile strength, the aluminum alloy EN AW 7075 T6 offers a high lightweight potential for structural components. Since its formability is limited at room temperature in the T6 temper state, the potential of this alloy for automotive bodies is only utilizable by adapted deep drawing processes. In recent years, process chains suited for warm and hot forming have been researched and developed. However, warm and hot forming solutions require additional process steps and a complex tooling system in comparison to cold forming processes. Alternatively, the forming of such blanks at room temperature in the W temper state is favorable since conventional tools can be used. The W temper state is a heat treatment condition achieved after solution heat treatment and subsequent quenching, which is characterized by an increased ductility. However, this condition is unstable, due to the onset of natural ageing. With increasing time after the quenching step, the strength of the material increases, which leads to a reduction of formability. Another phenomenon that occurs after quenching is the Portevin Le-Chatelier effect. This effect causes the formation of flow lines during cold forming and results in a decrease of ductility. Hence, the objective of the investigations was to determine the formability of EN AW 7075 as a function of the natural ageing time after solution heat treatment and quenching. Therefore, tensile tests of various aged samples were carried out. The results show a relation of the formability to the natural ageing time and a dependency on the quenching rate. Furthermore, a heat treatment strategy for EN AW-7075 was developed, that considers manufacturing processes like the cathodic dip coating. The influence of the quenching rate, ageing time and temperature as well as the influence of temperature of the paint baking process after the cathodic dip coating were considered. Therefore, a design of experiments and tensile tests were carried out. Thus, the deep drawing of EN AW-7075 at room temperature is particularly promoted.